Perlindungan Hak Cipta Terhadap Penerjemahan Lirik Lagu Konco Turu dalam Perspektif Keadilan - Ni Made Ayu Sukma Rindyartini; Bagus Gede Ari Rama; I Gede Agus Kurniawan; Kadek Julia Mahadewi (Locus: Jurnal Konsep Ilmu Hukum, 2025)
The development of digital technology makes it easier for people to access and distribute musical works, including through the translation of lag or lyrics into various languages. Although it is considered a creative expression, this practice raises legal problems because it has the potential to violate copyright as stipulated in Law Number 28 of 2014 concerning copyright. This study aims to analyze the legal regulation of the translation of song lyrics without permission and the legal protection of translation from the perspective of justice. The method used is normative juridical law research with a legal and conceptual approach. The results of the study show that the translation of song lyrics without permission is a violation of the economic and moral rights of the creator as stipulated in article 9 paragraph (1). Based on the theory of legal protection by Philipus M. Hadjon, the copyright legal system has provided preventive and repressive protection through regulation and sanctions. Judging from Robert M. Sherwood's theory and Aristotle's justice, this study shows that the protection of copyright law has been aligned with the principle of justice, although it still requires increasing legal awareness of the community.